Animal Language in the Quran: The Application of Charles Hockett’s Design Features - Izzaddin Ali, Wuria; Abdulrahman Abdulla, Ismail (International Journal of Psychosocial Rehabilitation, 2019)
The present paper aims at analyzing those Quranicversesthath talk about the fact that animals, in general, ants and birds in particular, like humansrhave their ownr communication system. It also tries to investigate the applicability of Charles Hockett’s design features for human andanimalncommunicationmsystems fromn a Quranic perspective. In order to achieve these aims, the researchers have quoted theversesthath narrate the events in which the non-humancreatures talkedd,or,r betterto sayy,communicated,d in a way that resembles human language. It has been hypothesized that the design features proposed by Hockett are fully applicable toanimalncommunication systemsm asfareas the Qurann is concerned. In the end, the researchers suggest that it is quite safe and sound to call the system by which animals interact with each other a language, like human language, not “animal communication system.”